2022
DOI: 10.3390/s22103961
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Algorithm for the Removal of Electromagnetic Interference Noise in Photoacoustic Endoscopic Image Processing

Abstract: Despite all the expectations for photoacoustic endoscopy (PAE), there are still several technical issues that must be resolved before the technique can be successfully translated into clinics. Among these, electromagnetic interference (EMI) noise, in addition to the limited signal-to-noise ratio (SNR), have hindered the rapid development of related technologies. Unlike endoscopic ultrasound, in which the SNR can be increased by simply applying a higher pulsing voltage, there is a fundamental limitation in leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Following the review of the title and abstract and, upon necessity, the full text further 187 records were rejected. After the reviewing process, a total of 36 original papers [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and 20 conference proceedings [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the review of the title and abstract and, upon necessity, the full text further 187 records were rejected. After the reviewing process, a total of 36 original papers [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and 20 conference proceedings [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
“…The US is widely adopted for investigating organs and soft tissues in the abdominal cavity. Indeed, 14 (25%) of the reviewed papers [ 29 , 37 , 44 , 47 , 49 , 50 , 53 , 60 , 62 , 67 , 69 , 72 , 76 , 81 ] have been focused on abdominal US imaging. In particular, studies focused on liver, kidney, spleen and bowel examinations.…”
Section: Resultsmentioning
confidence: 99%
“…He et al 183 proposed an attentionenhanced GAN with a modified U-Net generator to remove noise from PAM images, prioritizing fine-feature restoration. Gulenko et al 184 evaluated different CNN architectures and found that U-Net demonstrated higher efficiency and accuracy in removing electromagnetic interference noise from PAE systems.…”
Section: Overcoming Other Specified Issuesmentioning
confidence: 99%
“… 112 Deep learning has also been applied in specialized modalities such as improving Bessel-beam performance 113 and processing endoscopic images. 114 …”
Section: Pa Plus Deep Learningmentioning
confidence: 99%